Nutritional leucine supplementation attenuates cardiac failure in tumour‐bearing cachectic animals. Issue 5 (24th February 2016) - Toneto, Aline Tatiane; Ferreira Ramos, Luiz Alberto; Salomão, Emilianne Miguel; Tomasin, Rebeka; Aereas, Miguel Arcanjo; Gomes‐Marcondes, Maria Cristina Cintra
Abstract: Background: The condition known as cachexia presents in most patients with malignant tumours, leading to a poor quality of life and premature death. Although the cancer‐cachexia state primarily affects skeletal muscle, possible damage in the cardiac muscle remains to be better characterized and elucidated. Leucine, which is a branched chain amino acid, is very useful for preserving lean body mass. Thus, this amino acid has been studied as a coadjuvant therapy in cachectic cancer patients, but whether this treatment attenuates the effects of cachexia and improves cardiac function remains poorly understood. Therefore, using an experimental cancer‐cachexia model, we evaluated whether leucine supplementation ameliorates cachexia in the heart. Methods: Male Wistar rats were fed either a leucine‐rich or a normoprotein diet and implanted or not with subcutaneous Walker‐256 carcinoma. During the cachectic stage (approximately 21 days after tumour implantation), when the tumour mass was greater than 10% of body weight, the rats were subjected to an electrocardiogram analysis to evaluate the heart rate, QT‐c, and T wave amplitude. The myocardial tissues were assayed for proteolytic enzymes (chymotrypsin, alkaline phosphatase, cathepsin, and calpain), cardiomyopathy biomarkers (myeloperoxidase, tissue inhibitor of metalloproteinases, and total plasminogen activator inhibitor 1), and caspase‐8, ‐9, ‐3, and ‐7 activity. Results: Both groups of tumour‐bearing rats, especially the untreated group, had electrocardiography alterations that were suggestive of ischemia, dilated cardiomyopathy, and sudden death risk. Additionally, the rats in the untreated tumour‐bearing group but not their leucine‐supplemented littermates exhibited remarkable increases in chymotrypsin activity and all three heart failure biomarkers analysed, including an increase in caspase‐3 and ‐7 activity. Conclusions: Our data suggest that a leucine‐rich diet could modulate heart damage, cardiomyocyte proteolysis, and apoptosis driven by cancer‐cachexia. Further studies must be conducted to elucidate leucine's mechanisms of action, which potentially includes the modulation of the heart's inflammatory process.